Interfaces for Multiparty Videoconferences. - Buxton, W.; Sellen, Abigail; Sheasby, M. (K. Finn, A. Sellen, & S. Wilbur (Eds.), Video-mediated Communication, NJ.: Erlbaum., 1997)
We describe how conventional approaches to multiparty video conferences are limited in their support of participants' ability to: establish eye contact with other participants; be aware of who is visually attending to them; selectively listen to different, parallel conversations; make side comments to other participants and hold parallel conversations; perceive the group as a whole; share documents and artifacts; and see co-participants in relation to work-related objects. We present some design alternatives to these conventional videoconferencing approaches, describe the prototypes we have developed, and discuss their experimental evaluation.